Essential Oils Combined with Vitamin D3 or with Probiotic as an Alternative to the Ionophore Monensin Supplemented in High-Energy Diets for Lambs Long-Term Finished under Subtropical Climate - Lucía de G. Escobedo-Gallegos; Alfredo Estrada-Angulo; Beatriz I. Castro-Pérez; Jesús D. Urías-Estrada; Elizabeth Calderón-Garay; Laura Ramírez-Santiago; Yissel S. Valdés-García; Alberto Barreras; Richard A. Zinn; Alejandro Plascencia (Animals, 2023)
Supplementation with natural additives such as essential oils (EO) or probiotics has resulted in comparable growth performance to that of supplemental monensin in fattening lambs in hot environments. Supra-supplementation levels of vitamin D3 improved the carcass weight and dressing percentage of steers fattened under tropical conditions. We hypothesized that certain combinations of these natural additives could be complementary. For this reason, a feeding trial was carried out using 48 Pelibuey × Katahdin non-castrated male lambs (107 ± 14 d age; 17.9 ± 2.51 kg LW). Lambs were fed an 88:12 concentrate to forage ratio basal diet supplemented (dry matter basis, DMI) with: (1) no additive (CON); (2) 28 mg monensin/kg diet (MON); (3) 150 mg of essential oils containing a combination of thymol, eugenol, vanillin, guaiac, and limonene plus 0.12 mg vitamin D3 (EO + D3)/kg diet; and (4) 300 mg of essential oils containing a combination of carvacrol and cynamaldehyde plus 2 g probiotic (2.2 × 108 CFU of bacillus subtilis/kg diet, EO + BS). Lambs were grouped by initial weight and assigned within six weight groupings to 24 pens (2 lambs/pen, 6 replicas per treatment) in a randomized complete block design. The experiment lasted 121 days. Daily maximal THI exceeded the 80 “danger or “emergency” range for 119 days of the 121 days of the trial. Lambs supplemented with MON had similar DMI, growth performance, and dietary energetics to those of CON lambs. Lambs supplemented with EO + BS had a greater (9.2%, p ≤ 0.05) average daily gain (ADG) than the CON and MON groups due to enhanced (10.2%, p ≤ 0.05) dry matter intake. Thus, gain efficiency (GF) and estimated dietary energy were similar for CON, MON, and EO + BS. Lambs receiving EO + D3 had similar (0.254 vs. 0.262 kg/d) ADG but a lower DMI (8%, p < 0.05) compared with EO + BS lambs. Consequently, GF and estimated dietary net energy were greater (4.9 and 3.7%, respectively; p ≤ 0.05) for EO + D3 lambs. Even when ambient heat load was elevated, the efficiency of utilization of dietary energy (observed-to-expected dietary net energy) was close to 1.00 (0.992) expected for EO + D3 lambs. In contrast, efficiency of energy utilization was depressed by −4.4% for lambs on the other treatments. Compared with the other treatments, lambs receiving EO + D3 had greater longissimus muscle area (5.6%, p < 0.05) and lower kidney pelvic fat (21.8%, p ≤ 0.05). There were no treatment effects on shoulder tissue composition or whole cuts (expressed as % of cold carcass weight). Compared to CON, lambs that were fed with natural additives showed 3.5% lower (p ≤ 0.05) intestine mass. All supplemental additives decreased visceral fat mass, which was minimal with EO + D3 treatment. Combinations of essential oils with vitamins or probiotics were superior to antibiotic monensin in finishing diets for feedlot lambs. Combining EO with probiotics promoted DM intake and gain but not gain efficiency, while combining EO with vitamin D3 supra-supplementation increased dietary energy efficiency and improved some carcass characteristics in lambs fattening under high ambient heat loads.